Model Treffinger: Pengaruh terhadap Motivasi Belajar dan Kemampuan Berpikir Kreatif pada Materi Bunyi - Nilawati Tadjuddin; Mukarramah Mustari; Mela Puspita (Pendidikan Fisika Universitas Nurul Huda, 2020)
This research aims to determine the influence of students’ learning motivation using the Treffinger learning model and to determine the influence of students’ creative thinking skills using the Treffinger learning model. This research was conducted at SMPN 2 Jati Agung, South Lampung. The research method used was quasi-experimental. In taking the sample in this study using a purposive sampling technique, with class VIII A as an experimental class and class VIII B as a control class. The instruments in this research used learning motivation questionnaires and essay tests on creative thinking skills. Research results obtained using the t-test revealed the average score of the students’ learning motivation questionnaire in the experimental class is 87.6 and in the control class is 80.0, so that a score of tcount > ttable (6.019 > 1.996), and the average posttest score of students’ creative thinking skills in the experimental class is 80.3 and in the control class is 61.0, so that the score of tcount > ttable (7.589 > 1.996). It was concluded that there was an influence of Treffinger's learning model on the sound subject on students’ learning motivation and students’ creative thinking skills.